R & D : Teh Daun Kelor, Upaya Peningkatan Volume ASI di Kelurahan Cijoro Kabupaten Lebak Provinsi Banten Tahun 2022. - Anis Ervina; Rika Fitriyani; Sulis Sulis; Mila Lestari; Anita Purnama Sari; Pujawati Pujawati; Umul Bahriah (Jurnal Obstretika Scientia, 2022)
Moringa leaf tea is tea that comes from a leaf called Moringa Oleifera based on several studies that have many proven properties (Winarno, 2018). One of its properties is to increase milk production because it contains phytosterol compounds, namely alkaloids, saponins and flavonoids which function to increase and facilitate milk production (Purnanto, Himawati and Ajizah, 2020). Milk production is the result of breast stimulation by the hormone prolactin, this prolactin hormone is produced by the anterior pituitary gland. (Zakaria et al., 2016). The purpose of this study was to determine the effectiveness of Moringa leaf tea (moringa olifiera) on increasing the volume and perception of breast milk in breastfeeding mothers in the Cijoro Lebak Village, the Working Area of the Rangkasbitung Health Center in 2022. The type of research used is pre-experimental design, the population is breastfeeding mothers who are in the Cijoro Lebak Village, the Working Area of the Rangkasbitung Health Center in 2022, namely 307 people, and a sample of 17 people. Based on the results of the analysis, it was found that the perception of breastfeeding mothers increased by 14 respondents (76.5%) and while the average increase in breast milk volume was 78.1 grams or equivalent to 78.1 ml. Therefore, the community and health workers can use Moringa leaf tea as a way to solve problems in handling breastfeeding mothers who feel they are lacking breast milk.